(untitled) (Scientific journal of the Fergana State University, 2025)
The vitamin content in water extracts of local medicinal plants, specifically Rosehip (Rosa canina L.) and licorice (Glycyrrhiza glabra L.), was studied experimentally. To determine the vitamin content in the extracts, various sources were utilized: Vitamin B12 from Rhydburg Pharmaceuticals (Germany), vitamin C from Carl Roth GmbH (Germany), vitamin B9 from DSM Nutritional Products GmbH (Germany), and vitamins B1, B2, B3, B6, and PP from BLDPharm (China). HPLC-grade reagents such as water, acetonitrile, chemically pure acetic acid, and sodium hydroxide were also used. The vitamins were analyzed using an LC-40 Nexera Lite high-performance liquid chromatograph by Shimadzu (Japan). The water extract was prepared from a blend of rosehip fruits (Rosa canina L.) and licorice roots (Glycyrrhiza glabra L.) in a ratio of 75:25. This extract is found to be rich in vitamins. Based on its beneficial chemical composition, recommendations have been developed for its use in strengthening the immune system, treating upper respiratory tract diseases, and alleviating phlegm.